Standardization of Latency and Amplitude Values of Short, Middle and Long Latency Auditory Evoked Potentials in Adults - Pelaquim, Andressa; Sanfins, Milaine Dominici; Fornazieri, Marco Aurélio (International Archives of Otorhinolaryngology, 2023)
Introduction Auditory processing refers to the efficiency and effectiveness with which the central auditory nervous system uses auditory information. Middle- and long-latency auditory evoked potentials are objective electrophysiological tests that can complement the diagnosis of alterations involving central auditory processing.Objective To standardize latency and amplitude values for short-, middle-, and long-latency auditory evoked potentials in adults with normal hearing thresholds.Methods This is a cross-sectional study. Thirty-three adults with normal hearing thresholds, without hearing complaints, and with normal central auditory processing were evaluated. All underwent basic audiological evaluation, central auditory processing assessment, and short-, middle-, and long-latency auditory evoked potentials.Results Absolute latency and interpeak values for middle- and long-latency auditory evoked potentials were lower than internationally suggested. However, for the brainstem auditory evoked potential, the means were within the range considered as normal, as suggested in the equipment.Conclusion The present study provided measurements of normal latencies and amplitudes for short-, middle-, and long-latency auditory evoked potentials in adults.
Keywords: electrophysiology; hearing; adults; audiology